Application of remote sensing in thematic forestry: a systematic review of online research articles and forecasting its growth using the PRISMA framework - Ismail, Mohd Hasmadi; Yaakub, Nur Faziera; Ibrahim, Nur Fatihah (Malaysian Forester, 2024)
Research plays an important role in forestry, particularly in forest management. The wide range of current multispectral sensors available in remote sensing technology enables the enhancement of forest systems and management practices. This study employed the standard systematic review guidelines outlined in the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework to analyse articles published online regarding the usage of remote sensing over ten years (2010 to 2020). The review focused on the application of remote sensing data in selected thematic forestry areas, namely (i) forest management and conservation, (ii) forest inventory and survey, (iii) forest recreation and ecotourism, (iv) forest harvesting and operation, and (v) wildlife management and monitoring. Data and articles were sourced from the Scopus bibliographic database. The extracted themes were analysed using descriptive statistics in Excel, and XLSTAT forecast time series was applied to examine the trends of remote sensing applications until 2025. Based on the defined inclusion criteria, 157 articles were selected for the analysis. Results showed that forest management and conservation emerged as the main theme with the highest number of articles, indicating a growing interest in developing aspects of this field worldwide. Furthermore, the prediction analysis of scientific output on remote sensing in forestry themes showed an increasing trend until 2025. This study contributes to the academic, scientific, and institutional discourse, aiming to enhance the direction of research in this discipline, and proposes new scenarios of remote sensing technology for the improvement of forest resource management and conservation.